Resprouting increases seedling persistence likelihood after fire in a semelparous bamboo species - Cavallero, Laura; Blackhall, Melisa (Elsevier, 2022)
Chusquea culeou is a semelparous bamboo species which dominates the understorey of temperate forests and shrublands of Patagonia, South America. After the massive flowering, seeding and subsequent die-off, it provides an extraordinary amount of fine and dry fuel that increases wildfire likelihood, which in turn threatens the survival of its own offspring. In this context, we tested if this species could have alternative survival mechanisms which allows the persistence of the single seedling cohort, specifically evaluating two stages: seed and seedling. After a massive flowering event that occurred in summer 2010–11 and reached a regional scale in north-western Patagonia, we experimentally tested: 1) the effect of heat (90 °C, 120 °C, 150 °C) and/or ash on germination capacity of C. culeou seeds; and 2) the effect of low to moderate intensity fires on resprouting response of seedlings (<2 yr). Heating treatments inhibited seed germination, whereas most of the seedlings survived after their above-ground biomass was burned. Resprouting ability increased with maximum temperature reached at shoot base. Post-fire survival was considerably high, since 68% of pots had surviving shoots at the end of the experiment. In a scenario of wildfire occurrence after a massive flowering and subsequent die-off event, our experimental results suggest that resprouting ability right from the seedling stage might ensure the persistence of C. culeou populations. Also, the differential vegetative response of the seedlings to distinct fire-intensities could trigger distinct recovery trajectories in the understorey, generating an opportunity for regeneration of other trees and/or shrub species.